PERANCANGAN SISTEM INFORMASI AKADEMIK SEKOLAH MENENGAH PERTAMA BERBASIS WEB - David Oni Apaseray; Noberti Chandra Putra Tambay; Jayando Haloho; Heru Sutejo (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study focuses on the design of a comprehensive web-based academic information system for Junior High Schools. Observations reveal that the current academic data management system largely relies on manual and fragmented processes, leading to inefficiencies, susceptibility to input errors, data duplication, and limited real-time information access for students, teachers, and parents. To address these challenges, the Object-Oriented Analysis and Design (OOAD) approach was applied in the system's design phase. This methodology enables the visualization of system functionalities through Use Case Diagrams, core entity structures via Class Diagrams, object interaction flows using Sequence Diagrams, and key business processes like report card generation with Activity Diagrams. The resulting design is expected to provide an automated solution for academic data management, significantly enhance accuracy and operational efficiency, and establish an integrated platform that ensures quick and easy information access for all stakeholders within the school environment.